Traumatic posterolateral abdominal wall hernia in a pediatric patient - Christina M. Theodorou; Laura A. Galganski; Rebecca A. Stark (Elsevier, 2019)
Traumatic abdominal wall hernia (TAWH) is a relatively uncommon injury, with incidence estimates ranging from 1% to 9% of blunt abdominal trauma patients (1). Traumatic posterolateral abdominal wall hernia is an even less common subset of TAWH, in which intra- or extra-peritoneal contents herniate through a defect in the lumbar region within the superior or inferior lumbar triangles (2).The clinical presentation of traumatic posterolateral abdominal wall hernias range greatly, from abdominal wall ecchymosis to frank peritonitis. There is a paucity of reported cases in the pediatric surgical literature of traumatic abdominal wall hernias, and most of these cases are so-called 'handle-bar injuries,' resulting from bicycle crashes (3). We present a case report of a child who presented with a traumatic posterolateral abdominal wall hernia following a motor vehicle collision (MVC) and was found to have multiple intraabdominal injuries as well as a diffuse lumbar hernia with incarcerated bowel.